Sociology and Liturgy - Flanagan, K. author. aut Link
XI, 411 p.
Keywords: This is a study of the social construction and the impression management of the public forms of worship of Catholicism and Anglicanism. Interest centres on the dilemmas of the liturgical actors in handling a transaction riddled with ambiguities and potential misunderstandings. The study is an innovative effort to link sociology to theology in a way that serves to focus on an issue of social praxis.